La photographie à la Librairie centrale des Beaux-Arts – Éditions Albert Lévy (1906-1936) - Maud Allera (Les Cahiers de l'École du Louvre)
When Albert Lévy (1891–1976) took over the publishing house La Librairie Centrale des Beaux-Arts in 1919, it had enjoyed a certain fame since the late 19th century. The publications of Lévy, at the helm of the family business until 1936, were part of a period rich in critical developments, both for the revival of decorative arts and for that of the recognition of photography. The publishing house’s photographic archives, now in the Musée des Arts Décoratifs de Paris, also find themselves at the crossroads of early twentieth-century decorative arts and photography. From 1928, the publisher seems to have abandoned black-and-white photography in favour of stencil-coloured illustrations. Thus it was necessary to examine the roles occupied by photography and photographers in his editorial project and how the concession of the photographic laboratory of the Union Centrale des Arts Décoratifs, run by the Lévy family from 1907 to 1936, became part of its activities.